Longitudinal impact of asymptomatic malaria/HIV-1 co-infection on Plasmodium falciparum gametocyte transcript expression and transmission to Anopheles mosquitoes - Roberds, Ashleigh; Kifude, Carolyne; Oyieko, Janet; Ocholla, Stephen; Mutunga, James; Oullo, David; Waga, Charles; Li, Zhaozhang; Luckhart, Shirley; Stewart, V. Ann (Frontiers in Cellular and Infection Microbiology, 2022)
Despite significant developments towards malaria reduction, parasite transmission in the common context of HIV-1 co-infection and treatment for one or both infections has not been fully characterized. This is particularly important given that HIV-1 and malaria chemotherapies have the potential to alter gametocyte burden and mosquito infectivity. In this study, we examined 782 samples collected from a longitudinal cohort of 300 volunteers in the endemic region of Kisumu, Kenya, to define the impacts of HIV-1 co-infection, antiretroviral therapy (ART) plus trimethoprim-sulfamethoxazole (TS) and the antimalarials artemether/lumefantrine (AL) on Plasmodium falciparum gametocyte transcript prevalence and parasite transmission to the African malaria mosquito Anopheles gambiae. Using our highly sensitive digital droplet PCR (ddPCR) assay of three gametocyte specific transcript markers, we observed an overall gametocyte prevalence of 51.1% across all study groups and time points. After correcting for multiple comparisons, the factors of HIV-1 status, time, CD4+ T-cell levels and hematocrit were not predictive of gametocyte prevalence or transmission. Among those volunteers who were newly diagnosed with HIV-1 at enrollment, however, the initiation of ART/TS and AL at enrollment was associated with a significant reduction in gametocyte transcript prevalence in the subsequent month when compared to HIV-1 negative volunteers. To assess gametocyte transmissibility, volunteer blood samples were used in standard membrane feeding assays with laboratory-reared A. gambiae, with evidence of transmission confirmed by at least one of 25 dissected mosquitoes per sample positive for at least one midgut oocyst. Although HIV-1 status, CD4+ T-cell levels and hematocrit were not significantly associated with successful transmission to A. gambiae, we observed that 50% of transmission-positive blood samples failed to test positive by Plasmodium-specific 18S ribosomal RNA quantitative PCR (qPCR) and 35% failed to test positive for any gametocyte specific transcript marker by droplet digital (ddPCR). Overall, these findings highlight the complexity of HIV-1 malaria co-infection and the need to further define the unpredictable role of asymptomatic parasitemia in transmission to mosquitoes.